Empowering Education: The Millennial-Driven Paradigm of Learner-Centric Pedagogy - Sailaja, S.V.; Kashyap, A.M.N.; Sarada, T.; Rahman, Rashda (Edutechnium Journal of Educational Technology, 2024)
In the ever-evolving landscape of education, the emergence of the millennial generation has catalyzed a transformative shift towards learner-centric pedagogy. This paradigmatic evolution recognizes the unique needs, preferences, and characteristics of millennial learners, fostering an educational environment that places them at the center of the learning process. This abstract explores the key elements and justifications for adopting a millennial-driven approach to education. It examines the role of technology, individualized learning paths, collaborative learning experiences, and the empowerment of students as active agents in their educational journeys. By delving into these components, this abstract elucidates the rationale behind embracing this progressive educational model, offering insights into how it empowers both learners and educators to thrive in the 21st-century educational landscape.